Determinan Belanja Modal Untuk Membangun Kemandirian Keuangan Daerah - Ariyanto, Kevin; Nasiansenus Masdjojo, Gregorius (JURNAL LITBANG KOTA PEKALONGAN, 2025)
This study focuses on a quantitative approach aimed at explaining panel data regression analysis on the determinants of capital expenditure and its impact on regional financial independence. The data used includes Budget Realization Reports  from 2018 to 2022. Fixed Effect Model (FEM) is picked as the best model based on statistical model testing to do regression. The findings indicate that capital expenditure serves as a bridge connecting Local Own-Source Revenue and balancing funds includes General Allocation Funds, and Special Allocation Funds to financial independence through asset acquisition, regional asset improvement, and regional economic development. Capital expenditure funded by Local Own-Source Revenue, General Allocation Funds, and Special Allocation Funds has been proven to enhance Local Own-Source Revenue generation through the utilization of regional infrastructure and assets. This enables regions to gradually reduce dependency on government funding. In contrast, Revenue Sharing Funds do not significantly contribute to capital expenditure. Consequently, the expectation of increasing Local Own-Source Revenue through capital expenditure for acquiring fixed assets, which could enhance the region's capacity to deliver public services, remains unmet, ultimately failing to improve financial independence. The implications of this study can serve as a basis for local governments in formulating financial management strategies oriented toward enhancing fiscal independence